The Perfect Law of Liberty on Poverty and Wealth: A Precursor to Paul? - Blomberg, Craig L. (Tyndale bulletin, 2022)
Even as other tensions are resolved, some scholars continue to pit James against Paul with respect to their views on poverty and wealth. This paper first summarises the main contributions of James to the topic. Then it asks how far back in the letter-writing ministry of Paul can parallels to James be found. Recognizing that relative chronologies usually remain unaltered even if the deutero-Paulines are deemed pseudonymous, the survey looks at the key texts in the Pastorals, the Prison Epistles, 1-2 Corinthians and Romans, the Thessalonian letters and Galatians. It finds the most striking and informative parallel at the earliest point in the sequence, in Galatians 2:10. While acknowledging other possibilities, the study suggests that the most natural source for most of Paul’s teaching on poverty and wealth is, or is mediated by, James. The two authors also agree on what may be the unifying theme of New Testament theology - fulfilment of the Law - expressed in both of these writers particularly in the command to love one’s neighbour, which directly affects matters of care for the impoverished. A wedge should not be inserted between Paul and James on poverty and wealth; rather, they demonstrate striking similarities.